Pemerolehan Konjungtor pada Anak Usia Prasekolah - Yulianti Rasyid; Mita Domi Fella Henanggil; Nesa Riska Pangesti (Lingua Susastra, 2022)
This study aims to describe the acquisition of conjunction elements in preschool children. This research is focused on the acquisition of coordinating and subordinating conjunctions in preschool-aged children. The subject of this research is a 5 year old girl. The data in this study are utterances from 5-year-old girls which contain elements of coordinating and subordinating conjunctions. This study uses a qualitative descriptive research design. There are three stages of data analysis in this study, namely reduction, presentation, and drawing conclusions. The results of the study show that the conjunctions most frequently found in the speech of research subjects are coordinating conjunctions. The coordinating conjunctions found in the utterances of the research subjects are and, or, but, whereas, besides, moreover, only, except. The subordinating conjunctions found in the utterances of research subjects are if, if, for, so, before, after.